Foot hexadactyly, social implications and management in the African setting: Case report - Amouzou, Komla Sena; Joyce-Malonga-Loukoula, Elodie Lucrece; Kouevi-Koko, Tete Edem; Bakriga, Batarabadja; Abalo, Anani (The Turkish Journal of Pediatrics, 2018)
Hexadactyly of the foot, an abnormal congenital condition presenting as eight toes, is a rare malformation. We report the case of a ten-year-old girl, admitted to our orthopedic and reconstructive surgery department for a preaxial hexadactyly. The girl was abandoned by her parents at birth and stopped school early due to stigmatization. The goals of the surgical procedure were: social reintegration, gait improvement, ability to wear shoes comfortably, and improved appearance of the foot. The surgery was a medial resection of the supernumerary toes.
Keywords: Africa; congenital malformation; foot malformation; polydactyly